2016
DOI: 10.5811/westjem.2015.12.28781
|View full text |Cite
|
Sign up to set email alerts
|

There’s an App for That? Highlighting the Difficulty in Finding Clinically Relevant Smartphone Applications

Abstract: IntroductionThe use of personal mobile devices in the medical field has grown quickly, and a large proportion of physicians use their mobile devices as an immediate resource for clinical decision-making, prescription information and other medical information. The iTunes App Store (Apple, Inc.) contains approximately 20,000 apps in its “Medical” category, providing a robust repository of resources for clinicians; however, this represents only 2% of the entire App Store. The App Store does not have strict criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 3 publications
0
29
0
2
Order By: Relevance
“…Numerous medical applications already exist, for example, in the field of chronic disease management . Clinical use of well‐designed smartphone applications can provide a considerable added value for both patients and medical staff . Thanks to the enormous computing capacity of modern devices, as well as the additional possibility of internet storage (Cloud), clinical decision‐making tools have now become reality …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous medical applications already exist, for example, in the field of chronic disease management . Clinical use of well‐designed smartphone applications can provide a considerable added value for both patients and medical staff . Thanks to the enormous computing capacity of modern devices, as well as the additional possibility of internet storage (Cloud), clinical decision‐making tools have now become reality …”
Section: Discussionmentioning
confidence: 99%
“…12 Clinical use of well-designed smartphone applications can provide a considerable added value for both patients 16 and medical staff. 10 Thanks to the enormous computing capacity of modern devices, as well as the additional possibility of internet storage (Cloud), clinical decision-making tools have now become reality. 10 However, in the field of LVAD therapy, no smartphone applications have been implemented in the routine aftercare of patients to date, and only very few pilot studies have been conducted, with very small patient groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It remains difficult for an individual clinician to identify which medical apps are relevant among the morass of available software. For example, Wiechmann and colleagues searched for available apps that would be useful to Emergency Medicine clinicians . The authors reported that the iTunes App Store contains approximately 20 000 apps in its “Medical” category, representing 2% of the entire App Store.…”
mentioning
confidence: 99%